2015
DOI: 10.1002/piq.21178
|View full text |Cite
|
Sign up to set email alerts
|

Exploring User Acceptance of an Electronic Performance Support System

Abstract: This mixed methods research study aimed to explain and understand user acceptance of an electronic performance support system (EPSS) designed for the Crime Scene Investigation and Identification Units of the Turkish National Police. Quantitative data were collected from 209 police officers through a questionnaire to test relationships hypothesized in the technology acceptance model. At the same time, qualitative data were collected through interviews with 15 police officers to acquire an in‐depth understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…( 1) External performance support is not integrated into the system or the work interface and can also be paperbased, for instance. As such, users have to turn away from the target system and to break the work context in order to use the external EPSS (Gery, 1995;Mao, 2004;Sumuer and Yildirim, 2015). Early examples of external performance support are help desks, questions and answers Q&A, job aids, manuals, knowledge databases, and search engines (Gery, 1995;Nguyen et al, 2005;Nguyen and Hanzel, 2007;Gal and Nachmias, 2012).…”
Section: Electronic Performance Support Systems and Informal Workplac...mentioning
confidence: 99%
“…( 1) External performance support is not integrated into the system or the work interface and can also be paperbased, for instance. As such, users have to turn away from the target system and to break the work context in order to use the external EPSS (Gery, 1995;Mao, 2004;Sumuer and Yildirim, 2015). Early examples of external performance support are help desks, questions and answers Q&A, job aids, manuals, knowledge databases, and search engines (Gery, 1995;Nguyen et al, 2005;Nguyen and Hanzel, 2007;Gal and Nachmias, 2012).…”
Section: Electronic Performance Support Systems and Informal Workplac...mentioning
confidence: 99%
“…The system potentially be done continuously if a system has the ability to reduce effort of the users or taxpayers. Sumuer & Yildirim (2015) states that the perceived satisfaction of the users is a feeling free from content or discontent in accepting the information system of the whole benefits someone expects where the feeling is resulted from having interaction with the information system. In addition, each taxpayer is obligat ed to use the e-filing system as a method to report his annual tax return even though he is not satisfied with the e-filing system inas much as he will be sanctioned if he does not report his annual tax returns.…”
Section: Sem Resultsmentioning
confidence: 99%
“…Davis (1989) found that people's intention to use the system was influenced by the benefits and convenience of the system. In addition, several research ers (Adomavicius, Curley, Gupta, & Sanyal, 2013;Sumuer & Yildirim, 2015) found that the satisfaction and comfort of users of in formation systems greatly stimulated them to use it in the future. This research was conducted by using the taxpayers listed at Tax Service Office Pratama Pekanbaru Senapelan as the objects as never before has a research been conducted to find out the use of the e-filing in Pekanbaru City, Riau.…”
mentioning
confidence: 99%
“…Interface design describes how easy it is to use mobile AR. According to usability studies from other performance support systems, the interface design affected the perceived usefulness and ease of use in the intervention adoption (Kasvi & Vartiainen, 2000; Sumuer & Yildirim, 2015). Because mobile AR is delivered mostly on a mobile device with a small screen, the screen layout needs to be considered carefully to be viewed properly.…”
Section: Mobile Ar Approaches In Performance Supportmentioning
confidence: 99%